THE IMPORTANCE OF GRADUATE ATTRIBUTES IN PREPARING LAW STUDENTS FOR LEGAL PRACTICE - Marc Welgemoed; Deon Erasmus (Obiter, 2023)
The gap between university legal education and legal practice significantly contributes to the view that most law graduates are substantially underprepared for entry into legal practice. Consequently, this article suggests that an improvement in the training of law students, as far as preparing them for entry into legal practice is concerned, is necessary. It is argued that this preparation is supported by transformative constitutionalism – that is, after graduation, graduates will be expected to possess certain attributes that will ensure that they are ready for entry into legal practice. It is therefore necessary to investigate and evaluate such graduate attributes, as well as to ascertain the source of the need for such attributes. In this article, the Qualification Standard for the LLB degree, as the source stipulating the standard of proficiency for which the LLB degree should prepare graduates, is also discussed. This is followed by an evaluation of a baseline study into graduate attributes from the perspective of employers. Holistically seen, the qualification standard, as well as the graduate-attributes study, should provide an indication as to whether the LLB degree is adequately preparing law graduates for entry into legal practice. The qualification standard is set out and evaluated on whether, and to what extent, it aligns with the arguments put forth in this article. The research in this article has been conducted by way of a desktop study.